Trend Analysis and Purpose of Use of Some Important Plant and Animal Species of Ghandruk VDC, Nepal - Adhikari, Y.P.; Fischer, A. (Our Nature, 2011)
Ghandruk is one of the famous tourism VDC of Annapurna Conservation Areas (ACA). Trend analysis and propose of use of plants and animal species of Ghandruk Village Development Committee of Kaski district, western part of Nepal was carried out. A total of 54 plant species and 18 animal species with high local economic value were documented from structured questionnaire, interviews, key informants interviews, and focused group discussion with representatives and ACAP staffs. Trend analysis shows that most of the species increased during the past 20 years. All species are equally important for their purpose of uses. Michelia champaca, Schima wallichii, Castanopsis indica are very important trees for timber production. Quercus lamelossa, Q. semicarpifolia and Ficus roxburghii are very good fodder species. Alnus nepalensis colonizes landslides and degraded sites very successfully. Leaf extract of Ageratum conyzoides and fur of Lepus nigricollis is used to control bleeding from cuts and wounds. Medicinal plants, Terminalia bellirica, Terminalia chebula, Acorus calamus and Curcuma langa are used to control cough and bronchitis. The litter of plants is used to make compost fertilizer. Some animals were found the important medicinal purposes, some other used for control mouse populations. Some animals like Canis aureus and Martes flavigula, however, were found to be pests for domestic animals. DOI: 10.3126/on.v8i1.4319